Management of Migrant Health Insurance Scheme after Transferring Chaloem Phrakiat Health Centers and the Sub-district Health Promoting Hospitals to the Local Government Organizations in 4 Provinces - สายรัตน์ นิ่มอนงค์; เตชะเคหะกิจ วิน; สายรัตน์ ชิษณุชา (Journal of Health Science of Thailand, 2023)
This study aimed to explore problems, obstacles, opportunities, and suggestions regarding the financial management of Migrant Health Insurance Scheme (MHIS) after transferring Chaloem Phrakiat health centers and the sub-district health promoting hospitals to the local government organizations (LGO), using a qualitative approach. Documentary research was employed to reveal the current financial management of MHIS. A focus group discussion was conducted to gain insights about problems, obstacles, and suggestions pertaining to the regulation and implementation, consisting of the representatives from MHIS, hospitals, primary care health centers (PCHC), and provincial public health offices. Results indicated limited access to medical services among insurers at the PCHC under LGO. Further, concerns about unclear coverage of the health benefit package of the MWHI and technical problems regarding the budget transfer across the organizations were also raised, together with practical suggestions. Findings from this research could be used to inform policymakers about situations and suggestions of MHIS, with the purpose of improving health for the insured under this plan in the future.